Effect of the packaging on the quality of Salmo trutta macrostigma during chilled storage - Karakaya, E.; Duman, M. (Univ Putra Malaysia Press, 2016)
This study examined the effect of air (A), vacuum (VP) and modified atmosphere packaging (MAP) on the shelf-life of chilled Salmo trutta macrostigma. Fresh fish were stored in air, under vacuum and MAP (40% CO2: 60% N-2) under refrigeration (4 +/- 1 degrees C) for a period of 12 days. Total volatile basic nitrogen (TVB-N) for fish samples stored in A, under VP and MAP exceeded the limit value of 30 mg N/100 g fish muscle after 8, 10 and 12 days of storage, respectively. Thiobarbituric acid (TBA) values were variable in fish samples, indicative of no specific oxidative rancidity trend. Bacteria grew most quickly in fish samples stored in A, followed by those in VP and the lowest counts were with MAP. The observed shelf life of S. t. macrostigma was found to be 6 days in A, 10 days in VP and 12 days in MAP. (c) All Rights Reserved
Keywords: Salmo trutta macrostigma; Modified atmosphere packaging; Vacuum packaging; Quality parameters